منتخب اختصاصی قصص ِ قرآنی کا ماخذ: یہودی تفسیری متن مدراش ربی الیعیزر۔تاریخی تنقیدی جائزہ - Usmani Muhammad Tayyab (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2021)
Some Quranic stories completely are absent in the Bible, some of the Quranic stories have no parallels in the Bible, some Quranic stories have more details rather than The Bible. German jewish scholar Ribbi Abraham Gieger set a assumption About those stories which have no parallels in the Bible that Muhammad PBUH, the auther of Quranic text, has plagiarized and copied from Judeo-Christian apocryphal literature esepecially from the Jewish apocryphal source Midrash Pirke de-Rabbi Eli`ezer – a source from which critics. The majority of the Jewish, Christian critics and orientalists adopted his assumption. This research paper’s  questions was that according to Abraham Gieger and orientalists : is it true that the sources of Qur’ᾱnic stories what have no parallels in the Bible are plagiarized from Midrash Pirke de-Rabbi Eli`ezer. This paper shows that Midrash Pirke de-Rabbi Eli`ezer was developed after revelation of Quran, not quoted in any writings prior to the 9th century CE – well after the advent of the Qur'an. The critics of  Judeo-Christian apocryphal & midrashic literature provides sufficient evidence that Midrash Pirke de-Rabbi Eli`ezer was influenced by Quranic narrates. In conclusion, if anyone who has  sincerely studied dating of  Midrash Pirke de-Rabbi Eli`ezer and its dating should be able to  see that his sincerity negates taking data for making some Qur'ᾱnic stories  from Midrash Pirke de-Rabbi Eli`ezer.Keywords: Quranic stories  Judeo-Christian  apocryphal literature  Midrash  Plagiarism  Orientalist   Pirke de-Rabbi Eli`ezer